Organic-inorganic composite capillary crystalline waterproof material and preparation method thereof
Through the use of organic-inorganic composite permeable crystal waterproofing materials, the problems of low strength and poor durability of waterproofing agents in the prior art have been solved, efficient waterproofing performance and durability improvement are achieved, and are suitable for deep protection of concrete.
Patent Information
- Application Number
- CN202411801043.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-11
AI Technical Summary
In the prior art, the waterproofing agent has low strength, poor durability and corrosion resistance, making it difficult to effectively prevent moisture and harmful media from penetrating the inside of the concrete.
Using organic-inorganic composite permeable crystal waterproof material, it is prepared by composite silicone emulsion and inorganic silicate to form a composite protective layer, providing excellent waterproofness, mechanical strength and durability.
An effective waterproofing system is established inside the concrete, which significantly improves the compressive strength, penetration depth and water absorption rate of the waterproof materials, and enhances acid and alkali resistance and crack resistance.
Smart Images

Figure BDA0005178054330000091 
Figure BDA0005178054330000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to an organic-inorganic composite permeable crystallization waterproof material and a preparation method thereof. Background Art
[0002] Concrete, also known as concrete, is mainly made of cement, sand, stone, water, admixtures and other raw materials. After solidification and hardening, it becomes an uneven, porous artificial stone with a large number of pores and microcracks that are difficult to avoid. Various harmful media in the service environment often penetrate into the interior of the concrete material through these pores and microcracks, causing the concrete structure to gradually deteriorate from the surface to the inside, resulting in varying degrees of erosion. Long-term erosion will not only make concrete buildings less beautiful, but also reduce the durability of concrete and shorten the service life of concrete structures.
[0003] At present, the main ways to enhance the durability of concrete are to optimize the mix ratio, optimize the design and construction plan, and perform surface protection. Among them, optimizing the mix ratio and optimizing the design and construction plan are mainly used for new concrete projects. These two methods have been extensively studied and have achieved good results. Surface protection can be used not only for existing concrete projects, but also for new concrete projects, but there are still few related studies on surface protection methods, and they lack systematicity. At present, the mainstream surface protection agents on the market are waterproofing agents, mainly organic waterproofing agents and inorganic waterproofing agents, but each of them has certain shortcomings. Organic waterproofing agents have good waterproofing effects, convenient construction, and are not restricted by the shape of the construction substrate, but they fail quickly and cannot resist the influence of the external environment together with concrete. They also have low strength and poor aging resistance; inorganic waterproofing agents are completely compatible with concrete and can improve cracks, but their force is small and it is difficult to resist large deformations. Therefore, it is of great significance to develop a penetrating crystallization waterproofing material that can combine the advantages of both organic and inorganic waterproofing agents for the maintenance of concrete. Summary of the invention
[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an organic-inorganic composite permeable crystallization waterproof material and a preparation method thereof, so as to solve the problems of low strength, poor durability and corrosion resistance of the waterproofing agent in the prior art.
[0005] The technical solution of the present invention to solve the above technical problems is as follows: an organic-inorganic composite permeable crystallization waterproof material is provided, and the raw materials for preparing the waterproof material include the following components in parts by weight: 30-50 parts of polysiloxane emulsion, 1-5 parts of magnesium fluorosilicate, 2-6 parts of nano silicon dioxide, 5-15 parts of sodium methyl silicate, 0.5-2 parts of triisopropanolamine, 1-3 parts of polycarboxylic acid water reducer, 1-3 parts of sodium polyacrylate, 4-8 parts of potassium silicate, 2-5 parts of lithium silicate and 35-55 parts of water;
[0006] The raw materials for preparing the polysiloxane emulsion include the following components in parts by mass: 15 to 25 parts of dodecyltriethoxysilane, 5 to 15 parts of 3-aminopropyltriethoxysilane, 10 to 20 parts of triethoxysilane, 10 to 20 parts of ethyl silicate, 20 to 30 parts of ethanol, 15 to 25 parts of water and 1 to 2 parts of an emulsifier.
[0007] The invention has the following beneficial effects: the polysiloxane emulsion contains a siloxane (Si-O-Si) main chain structure, has excellent hydrophobicity, can form a continuous waterproof polymer film on the surface of a substrate, the film is insoluble in water and has excellent chemical stability, and can effectively prevent the penetration of liquid water; at the same time, the siloxy group (Si-OH) in the polysiloxane can react with the hydroxyl group (-OH) in the cement-based material to form a siloxane bond (Si-O-Si), thereby significantly enhancing the bonding force between the coating and the substrate; magnesium fluorosilicate can improve the activity of the siloxane group, accelerate the chemical reaction between the polysiloxane emulsion and the hydroxyl group on the surface of the substrate, and enhance the bonding force and compactness of the coating; at the same time, magnesium fluorosilicate reacts with calcium ions (Ca) in the substrate to form a siloxane bond (Si-O-Si). 2+ ) or other cations react to form fluorosilicate crystals, which work together with the polysiloxane film to form an organic-inorganic composite protective layer, which not only provides excellent waterproofness but also enhances the durability and corrosion resistance of the coating.
[0008] Lithium silicate has strong permeability, and the lithium ions (Li + ) and silicate ions (SiO4 2- ) has a very high diffusion capacity and can penetrate into the pores and microcracks of concrete or other substrates. Then the silicate ions react with free calcium hydroxide (Ca(OH)2 inside the substrate to form dense calcium silicate hydrate (CSH gel), and further transform into stable crystal forms (such as calcium aluminate, calcium silicate crystals) in the local environment. These crystals are combined by chemical bonds to form rigid fillers, which effectively close the pores and microcracks, prevent the penetration of moisture and harmful ions, thereby reducing the damage of corrosive substances to the substrate, and also improve the mechanical strength of the substrate. At the same time, the flexibility of CSH gel can buffer the effects of thermal stress or mechanical stress on the substrate and delay the expansion of microcracks. When potassium silicate comes into contact with the substrate, it reacts rapidly with Ca(OH)2 to form rigid calcium silicate (CSH gel) and potassium ions (K + ), K +It has a high hydration capacity and can stably combine with the silicate radical to generate potassium silicate modified silicate crystals (KCSH) with high hardness. This reaction mainly occurs in the surface layer and shallow cracks of the substrate, which can quickly fill pores and cracks, enhance the hardness of the surface structure, and form a high-strength protective barrier. Lithium silicate has a small molecular weight and can penetrate into deep cracks and capillaries to repair the internal structure of the substrate; potassium silicate has a large molecular weight and a fast reaction speed, and mainly acts on surface cracks and pores. The two act on the deep and surface layers of the substrate respectively, distributed in cracks and pores of different depths, forming a multi-level silicate crystal network, improving the overall density and durability of the waterproof material; nano-SiO2 acts as a filler to fill fine pores, and can combine with the silicate network of lithium silicate and potassium silicate to further enhance the density and water penetration resistance of the coating.
[0009] The organic film of polysiloxane in the waterproof material provided by the present invention is combined with the silicate network of inorganic silicate to form a composite protective layer, which has excellent water repellency and provides high mechanical strength and durability.
[0010] On the basis of the above technical solution, the present invention can also be improved as follows:
[0011] Furthermore, the raw materials for preparing the waterproof material include the following components in parts by mass: 40 parts of polysiloxane emulsion, 2 parts of magnesium fluorosilicate, 3 parts of nano-silicon dioxide, 10 parts of sodium methyl silicate, 1 part of triisopropanolamine, 2 parts of polycarboxylic acid water reducer, 2 parts of sodium polyacrylate, 6 parts of potassium silicate, 3 parts of lithium silicate and 45 parts of water.
[0012] Furthermore, the raw materials for preparing the polysiloxane emulsion include the following components in parts by mass: 20 parts of dodecyltriethoxysilane, 10 parts of 3-aminopropyltriethoxysilane, 15 parts of triethoxysilane, 15 parts of ethyl silicate, 30 parts of ethanol, 15 parts of water and 2 parts of emulsifier.
[0013] Furthermore, the emulsifier is Tween 80.
[0014] The present invention also provides a method for preparing the above-mentioned organic-inorganic composite permeable crystallization waterproof material, comprising the following steps:
[0015] (1) adding dodecyl triethoxysilane, 3-aminopropyl triethoxysilane, triethoxysilane and ethyl silicate to ethanol in sequence, stirring evenly, then adding water and an acid catalyst, heating to 60° C., stirring for 30 to 60 minutes, then adding an emulsifier, stirring at 60° C. at a stirring rate of 2000 to 5000 rpm for 30 minutes, to obtain a polysiloxane emulsion;
[0016] (2) adding sodium methyl silicate to water, heating until dissolved, then cooling to room temperature, sequentially adding nano silicon dioxide, magnesium fluorosilicate, triisopropanolamine, polycarboxylic acid water reducer and sodium polyacrylate, lithium silicate and potassium silicate, mixing to obtain an inorganic mixed solution;
[0017] (3) Add the inorganic mixed solution into the polysiloxane emulsion and stir to obtain the product.
[0018] On the basis of the above technical solution, the present invention can also be improved as follows:
[0019] Furthermore, the acid catalyst is hydrochloric acid.
[0020] Furthermore, after the emulsifier is added in step (1), nitrogen is continuously introduced during stirring.
[0021] Furthermore, after mixing in step (2), ultrasonic treatment is performed at a frequency of 20 kHz for a time of 10 to 20 minutes.
[0022] Furthermore, in step (2), sodium methyl silicate is added to water and the temperature is raised to 85-95°C.
[0023] Furthermore, the stirring process parameter in step (3) is stirring at 600 rpm for 30 to 60 min.
[0024] The present invention has the following beneficial effects:
[0025] 1. The waterproof material provided by the present invention is based on a composite preparation method of an organosiloxane emulsion and an inorganic silicate, and is used to prepare a new type of fully water-permeable crystalline concrete self-waterproof material, which reacts with cement hydration products to form water-insoluble crystals, thereby establishing a waterproof system inside the concrete with excellent effects.
[0026] 2. The waterproof material provided by the present invention uses components such as siloxane substances, nano-silicon dioxide, magnesium fluorosilicate and silicate, and has better weather resistance, strength, crack resistance and corrosion resistance than traditional waterproof coatings, especially in applications under high humidity and acid-base environments, and performs more stably.
[0027] 3. The raw materials used in the present invention, such as magnesium fluorosilicate, lithium silicate, nano-silicon dioxide and polysiloxane coating, do not contain harmful organic solvents, have low VOC emissions, and meet green environmental protection requirements.
[0028] 4. The compressive strength of the waterproof material provided by the present invention can reach 49MPa, the penetration depth is about 9mm, and the water absorption rate is as low as about 4%. It has excellent protective effect in application scenarios such as underground engineering and crack repair that require deep protection. DETAILED DESCRIPTION
[0029] The principles and features of the present invention are described below in conjunction with the examples, which are only used to explain the present invention and are not intended to limit the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0030] Embodiment 1:
[0031] The present embodiment provides an organic-inorganic composite penetrating crystalline waterproof material. The raw materials for preparing the waterproof material include the following components in parts by mass: 40 parts of polysiloxane emulsion, 2 parts of magnesium fluorosilicate, 3 parts of nano-silicon dioxide, 10 parts of sodium methyl silicate, 1 part of triisopropanolamine, 2 parts of polycarboxylic acid water reducer, 2 parts of sodium polyacrylate, 6 parts of potassium silicate, 3 parts of lithium silicate and 45 parts of distilled water.
[0032] This embodiment also provides a method for preparing the above-mentioned organic-inorganic composite permeable crystallization waterproof material, comprising the following steps:
[0033] (1) Add 30 parts of ethanol, 20 parts of dodecyltriethoxysilane, 10 parts of 3-aminopropyltriethoxysilane, 15 parts of triethoxysilane and 15 parts of ethyl silicate into a three-necked flask, stir evenly, then add 15 parts of deionized water and 1 part of hydrochloric acid to start the hydrolysis reaction, heat to 60° C., and stir for 45 minutes; then add 2 parts of Tween 80, continue to introduce nitrogen, control the reaction temperature at 60° C., and stir at a stirring speed of 3000 rpm for 30 minutes to obtain a polysiloxane emulsion;
[0034] (2) adding sodium methyl silicate to distilled water, heating to 90° C., stirring to dissolve it, then cooling the solution to room temperature, sequentially adding nano-silicon dioxide, magnesium fluorosilicate, triisopropanolamine, polycarboxylic acid water reducer and sodium polyacrylate, lithium silicate and potassium silicate, and ultrasonically treating at 20 kHz for 15 min to obtain an inorganic mixed solution;
[0035] (3) Slowly add the inorganic mixed solution into the polysiloxane emulsion and stir at a stirring speed of 600 rpm for 30 minutes to obtain the product.
[0036] Embodiment 2:
[0037] The present embodiment provides an organic-inorganic composite penetrating crystalline waterproof material. The raw materials for preparing the waterproof material include the following components in parts by mass: 45 parts of polysiloxane emulsion, 3 parts of magnesium fluorosilicate, 4 parts of nano-silicon dioxide, 5 parts of sodium methyl silicate, 1.5 parts of triisopropanolamine, 2 parts of polycarboxylic acid water reducer, 1 part of sodium polyacrylate, 4 parts of potassium silicate, 3 parts of lithium silicate and 50 parts of distilled water.
[0038] This embodiment also provides a method for preparing the above-mentioned organic-inorganic composite permeable crystallization waterproof material, comprising the following steps:
[0039] (1) Add 20 parts of ethanol, 15 parts of dodecyltriethoxysilane, 5 parts of 3-aminopropyltriethoxysilane, 10 parts of triethoxysilane and 10 parts of ethyl silicate into a three-necked flask, stir evenly, then add 15 parts of deionized water and 1 part of hydrochloric acid, start the hydrolysis reaction, heat to 60° C., and stir for 30 minutes; then add 1 part of Tween 80, continue to introduce nitrogen, control the reaction temperature at 60° C., and stir at a stirring speed of 4000 rpm for 30 minutes to obtain a polysiloxane emulsion;
[0040] (2) adding sodium methyl silicate to distilled water, heating to 90° C., stirring to dissolve it, then cooling the solution to room temperature, sequentially adding nano-silicon dioxide, magnesium fluorosilicate, triisopropanolamine, polycarboxylic acid water reducer and sodium polyacrylate, lithium silicate and potassium silicate, and ultrasonically treating at 20 kHz for 15 min to obtain an inorganic mixed solution;
[0041] (3) Slowly add the inorganic mixed solution into the polysiloxane emulsion and stir at a stirring speed of 600 rpm for 30 minutes to obtain the product.
[0042] Embodiment 3:
[0043] The present embodiment provides an organic-inorganic composite penetrating crystallizing waterproof material. The raw materials for preparing the waterproof material include the following components in parts by mass: 35 parts of polysiloxane emulsion, 4 parts of magnesium fluorosilicate, 2 parts of nano-silicon dioxide, 15 parts of sodium methyl silicate, 2 parts of triisopropanolamine, 3 parts of polycarboxylic acid water reducer, 3 parts of sodium polyacrylate, 8 parts of potassium silicate, 5 parts of lithium silicate and 40 parts of distilled water.
[0044] This embodiment also provides a method for preparing the above-mentioned organic-inorganic composite permeable crystallization waterproof material, comprising the following steps:
[0045] (1) Add 30 parts of ethanol, 25 parts of dodecyltriethoxysilane, 15 parts of 3-aminopropyltriethoxysilane, 20 parts of triethoxysilane and 20 parts of ethyl silicate into a three-necked flask, stir evenly, then add 25 parts of deionized water and 1 part of hydrochloric acid, start the hydrolysis reaction, heat to 60° C., and stir for 60 minutes; then add 1 part of Tween 80, continue to introduce nitrogen, control the reaction temperature at 60° C., and stir at a stirring speed of 2500 rpm for 30 minutes to obtain a polysiloxane emulsion;
[0046] (2) adding sodium methyl silicate to distilled water, heating to 90° C., stirring to dissolve it, then cooling the solution to room temperature, sequentially adding nano-silicon dioxide, magnesium fluorosilicate, triisopropanolamine, polycarboxylic acid water reducer and sodium polyacrylate, lithium silicate and potassium silicate, and ultrasonically treating at 20 kHz for 15 min to obtain an inorganic mixed solution;
[0047] (3) Slowly add the inorganic mixed solution into the polysiloxane emulsion and stir at a stirring speed of 600 rpm for 30 minutes to obtain the product.
[0048] Comparative Example 1:
[0049] This comparative example provides a waterproof material, and the raw materials for preparing the waterproof material include the following components in parts by mass: 40 parts of styrene-acrylic emulsion (6062), 2 parts of magnesium fluorosilicate, 3 parts of nano-silicon dioxide, 10 parts of sodium methyl silicate, 1 part of triisopropanolamine, 2 parts of polycarboxylic acid water reducer, 2 parts of sodium polyacrylate, 6 parts of potassium silicate, 3 parts of lithium silicate and 45 parts of distilled water.
[0050] This comparative example also provides a method for preparing the above waterproof material, comprising the following steps:
[0051] (1) adding sodium methyl silicate to distilled water, heating to 90° C., stirring to dissolve, then cooling the solution to room temperature, sequentially adding nano-silicon dioxide, magnesium fluorosilicate, triisopropanolamine, polycarboxylic acid water reducer and sodium polyacrylate, lithium silicate and potassium silicate, and ultrasonically treating at 20 kHz for 15 min to obtain an inorganic mixed solution;
[0052] (2) Slowly add the inorganic mixed solution into the styrene-acrylic emulsion and stir at a stirring speed of 600 rpm for 30 minutes to obtain the product.
[0053] Comparative Example 2:
[0054] Use commercially available penetrating crystalline waterproof coating, brand: Pioneer / Pioneer, specification model: JX-SJ.
[0055] Experimental example:
[0056] The waterproof materials prepared in Examples 1-3 and Comparative Examples 1-2 of the present invention were tested as follows:
[0057] Compressive strength test: After the concrete compressive test piece is formed, it is placed indoors for 24 hours before demolding. The waterproof materials obtained by spraying Example 1-3 and Comparative Example 1-2 with a spraying age of 1 day and the blank test piece are immediately sprayed with clean water in the same manner. The remaining test pieces are placed in a standard curing box for curing. When the test pieces are cured for 3d, 7d, and 28d, respectively, they are taken out and dried for 1d, and then the waterproof material is sprayed to test its compressive strength.
[0058] Penetration depth test: refer to JC / T2235-2014 "Silica Protective Agent for Concrete" for penetration depth test. In the experiment, the tested base sample after reaching the age will be split and divided equally, the base material will be immersed in water for 2-3 minutes, the hydrophobic area will be observed, and 10 points will be marked in the concrete protection area to measure the distance from the concrete surface and calculate the average value.
[0059] Water absorption test: After treating the substrate with waterproof material, place it in a drying oven until it reaches constant weight, wipe the surface with a damp cloth, and then soak the test block in water. After one day, take out the test block, weigh the mass at each time, and calculate the water absorption.
[0060] The test results are shown in Table 1:
[0061] Table 1 Waterproof material performance test results
[0062]
[0063] It can be seen from the data in the table that the waterproof material prepared in the present application has better performance in compressive strength, penetration depth and water absorption rate. The penetration depth is increased by about 50% compared with the control group. The waterproof material penetrates deeply into the substrate and has a stronger overall bonding force with the substrate.
[0064] Acid and alkali corrosion resistance test: Refer to GB / T 50082-2009 "Standard for test methods of long-term performance and durability of ordinary concrete" to carry out acid, alkali and salt corrosion resistance test of concrete. The concrete test blocks coated with each group of waterproof materials were weighed and immersed in 3% HCl, 3% NaOH and 5% Na2SO4 solutions respectively. The mass change was measured after 7 days. The specific test results are shown in Table 2.
[0065] Table 2 Change in mass of test block for acid and alkali corrosion resistance test (%)
[0066] Experimental Group 3% HCl 3% NaOH <![CDATA[5%Na2SO4]]> Example 1 -2.65 2.83 2.32 Example 2 -3.15 2.85 2.18 Example 3 -3.51 3.04 2.64 Comparative Example 1 -5.74 4.85 5.04 Comparative Example 2 -4.95 4.21 3.87 Blank example -6.92 5.96 6.21
[0067] The results show that after being treated with the waterproof material prepared by the present invention, the change in the mass of the concrete is significantly reduced, indicating that the waterproof material prepared by the present invention can effectively prevent the intrusion of acid and alkali.
[0068] Anti-cracking test: The test was carried out in accordance with the relevant provisions of Article 9 of the current national standard "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The experimental results are shown in Table 3.
[0069] Table 3 Results of crack area and crack reduction rate
[0070]
[0071] The crack area of the test pieces sprayed with the waterproof material prepared by the present invention was reduced after 24 hours, and the number of cracks in Example 1 and Example 2 was reduced to 6. At the same time, the average crack area of each crack decreased with the increase of the brushing amount. Compared with the blank group, the average crack area of 96.15mm 2 The average crack area was reduced by more than 45%. It can be seen that the waterproof material prepared by the present invention has a more obvious inhibitory effect on early cracking of concrete.
[0072] In summary, the waterproof material prepared by the present invention has relatively excellent performance in terms of compressive strength, water absorption, corrosion resistance, acid and alkali resistance, and crack resistance.
[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An organic-inorganic composite permeable crystallization waterproof material, characterized in that: The raw materials for preparing the waterproof material include the following components in parts by weight: 30-50 parts of polysiloxane emulsion, 1-5 parts of magnesium fluorosilicate, 2-6 parts of nano silicon dioxide, 5-15 parts of sodium methyl silicate, 0.5-2 parts of triisopropanolamine, 1-3 parts of polycarboxylic acid water reducer, 1-3 parts of sodium polyacrylate, 4-8 parts of potassium silicate, 2-5 parts of lithium silicate and 35-55 parts of water; The raw materials for preparing the polysiloxane emulsion include the following components in parts by mass: 15 to 25 parts of dodecyltriethoxysilane, 5 to 15 parts of 3-aminopropyltriethoxysilane, 10 to 20 parts of triethoxysilane, 10 to 20 parts of ethyl silicate, 20 to 30 parts of ethanol, 15 to 25 parts of water and 1 to 2 parts of emulsifier.
2. The organic-inorganic composite permeable crystallization waterproof material according to claim 1, characterized in that: The raw materials for preparing the waterproof material include the following components in parts by mass: 40 parts of polysiloxane emulsion, 2 parts of magnesium fluorosilicate, 3 parts of nano silicon dioxide, 10 parts of sodium methyl silicate, 1 part of triisopropanolamine, 2 parts of polycarboxylic acid water reducer, 2 parts of sodium polyacrylate, 6 parts of potassium silicate, 3 parts of lithium silicate and 45 parts of water.
3. The organic-inorganic composite permeable crystallization waterproof material according to claim 1 or 2, characterized in that: The raw materials for preparing the polysiloxane emulsion include the following components in parts by mass: 20 parts of dodecyltriethoxysilane, 10 parts of 3-aminopropyltriethoxysilane, 15 parts of triethoxysilane, 15 parts of ethyl silicate, 30 parts of ethanol, 15 parts of water and 2 parts of emulsifier.
4. The organic-inorganic composite permeable crystallization waterproof material according to claim 3, characterized in that: The emulsifier is Tween 80.
5. The method for preparing the organic-inorganic composite permeable crystallization waterproof material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) adding dodecyl triethoxysilane, 3-aminopropyl triethoxysilane, triethoxysilane and ethyl silicate to ethanol in sequence, stirring evenly, then adding water and an acid catalyst, heating to 60° C., stirring for 30 to 60 minutes, then adding an emulsifier, stirring at 60° C. at a stirring rate of 2000 to 5000 rpm for 30 minutes, to obtain a polysiloxane emulsion; (2) adding sodium methyl silicate to water, heating until dissolved, then cooling to room temperature, sequentially adding nano silicon dioxide, magnesium fluorosilicate, triisopropanolamine, polycarboxylic acid water reducer and sodium polyacrylate, lithium silicate and potassium silicate, mixing to obtain an inorganic mixed solution; (3) Add the inorganic mixed solution into the polysiloxane emulsion and stir to obtain the product.
6. The preparation method according to claim 5, characterized in that: The acid catalyst is hydrochloric acid.
7. The preparation method according to claim 5, characterized in that: After the emulsifier is added in step (1), nitrogen is continuously introduced during stirring.
8. The preparation method according to claim 5, characterized in that: After mixing in step (2), ultrasonic treatment is performed at a frequency of 20 kHz for a time of 10 to 20 minutes.
9. The preparation method according to claim 5, characterized in that: In step (2), sodium methyl silicate is added to water and then heated to 85-95°C.
10. The preparation method according to claim 5, characterized in that: The stirring process parameter in step (3) is stirring at 600 rpm for 30 to 60 minutes.